Kajian Teologis Penggembalaan Reformatoris dalam Semangat Si Tou Timou Tumou Tou - Kansil, Yuansari; Lantemona, Herdianto; Runtuwene, Hendry C. M. (Educatio Christi, 2025)
The purpose of this article is to examine and explain the Reformatory Shepherding Theology and its relationship to the spirit of Si Tou Timou Tumou Tou in the aspect of church life. The statement of the problem is the lack of spirit of solidarity and the lack of strong theological aspects that are included in ecclesiastical shepherding. By using a qualitative approach and literature method, the results of the research concern the significance of Reformatory Shepherding Theology based on the spirit of reformation and the return to the Bible as a benchmark for theology and the doctrine of the Sovereignty of God is emphasized, then shepherding is strengthened and in the spirit of Si Tou Timou Tumou Tou the sense of solidarity to love others is strengthened and implemented in ecclesiastical shepherding. It is hoped that the concept and praxis of reformatory shepherding and Si Tou Timou Tou can be the driving force for the church to carry out comprehensive shepherding for the faith growth of the people.